Rethinking Monetary Policy: The case for adopting NGDP targeting in Britain - Damian Pudner (Institute of Economic Affairs (IEA), 2025)
The existing monetary framework of the Bank of England fails to manage supply-side shocks and financial crises effectively, which leads to economic volatility and potential policy errors. Targeting the growth path of nominal GDP would provide a more stable and predictable macroeconomic environment by focusing on total nominal spending rather than a rigid inflation target. Nominal GDP targeting reduces policy uncertainty by minimising discretionary decision-making, improving transparency, and better anchoring expectations for businesses and financial markets. Establishing a nominal GDP futures market could provide real-time guidance for policymakers, while enhanced data collection and market communication would facilitate a smooth transition. By stabilising total nominal spending, nominal GDP targeting supports long-term economic stability, reducing volatility in output and employment while ensuring a more growth-friendly policy framework. The Bank of England's failure to anticipate inflationary trends has undermined trust in its decision-making. A transparent and predictable nominal GDP-based framework would rebuild confidence in monetary policy.
Keywords: 330